パラメトリック曲面のための高速光線追跡表示 - Maciejewski, Anthony A., author; Information Processing Society of Japan, publisher (Colorado State University. Libraries, 1986)
Algorithms for ray tracing parametric surfaces are in general too computationally expensive to be widely applicable. The algorithm presented here combines well-known graphics procedures with a modified Newton iteration to provide a computationally efficient means of including parametric surfaces in a ray traced image. By allowing only planar surfaces to be reflective and/or refractive the resulting high degree of ray coherence is utilized to make the algorithm incremental and results in an order of magnitude improvement in computation speed over existing algorithms.
Computationally efficient ray tracing of parametric surfaces
Abstract also in Japanese.
Keywords: ray-surface intersection; intersection calculations; ray coherence; CAD/CAM modelling; realistic images